A novel aminotriazole-based NHC complex for the design of gold(i) anti-cancer agents: synthesis and biological evaluation1. Issue 6 (10th June 2015) - Serebryanskaya, T. V.; Zolotarev, A. A.; Ott, I.
<x xml:space="preserve">Abstract</x> A novel gold(i) complex based on an aminotriazole N-heterocylic carbene ligand represents a promising scaffold for the design of anticancer bioorganometallics.